Processing of XML Descriptions of OTP - Kubát, Petr (Vysoké učení technické v Brně. Fakulta informačních technologií, 2013)
Tato práce se zaměřuje na návrh a implementaci modulárního programu pro zpracování XML popisu OTP klíčů používaných především v zařízeních od výrobců Yubico a RSA. Zároveň také práce popisuje návrh a implementaci modulu pro vložení získaných informací do adresářového serveru 389DS. Součástí práce je seznámení s OTP, standartem PSKC a protokolem LDAP. Dále je v práci uveden návrh a implementace obou částí programu. V závěru práce rozebírá možnosti dalšího vývoje aplikace.

The focus of this thesis is the design and implementation of a modular application for parsing XML descriptions of OTP keys used mainly by hardware solutions of RSA and Yubico. The thesis also describes the design and implementation of a module used to upload the parsed information onto a 389DS directory server. This thesis acquaints the reader with the basics of one time passwords, the PSKC standard and the LDAP protocol. Finally this thesis analyzes the possibilities of future development of the application.
Processing of XML Descriptions of OTP
Keywords: PSKC; správa uživatelských účtů; LDAP; OTP; Yubikey; RSA; SecurID; 389DS; PSKC; identity management; LDAP; OTP; Yubikey; RSA; SecurID; 389DS